STUDY THE CHARACTERISTICS OF HEAT ENERGY IN THE AUTONOMIC SOLAR SYSTEM - Khuzhakulov Saydulla Mirzaevich , Khamraev Sardor Ilkhomovich , Mamedova Dilora Nusurovna , Kamolov Behzodjon Ilkhomovich , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article highlights the issues connected with the use of solar energy in heating rural houses, and economizes the energy supply on the account of autonomizing solar renewable energy. Furthermore, according to the potential of solar energy, data of the heat load on the issues of the heating houses and hot water supply were found. Besides, autonomizing heat system was recommended to one storey houses in rural areas and its characteristics were conducted widely.